Infection, Dissemination, and Replication of Urban and Sylvatic Strains of Dengue Virus Type 2 (Flaviviridae: Flavivirus) in Australian Aedes aegypti (Diptera: Culicidae). Issue 3 (18th January 2021) - Hall-Mendelin, Sonja; Pyke, Alyssa T; Ramirez, Ana L; Staunton, Kyran M; Burtonclay, Peter; McMahon, Jamie; Barcelon, Jean; van den Hurk, Andrew F
Abstract: The dengue viruses (DENVs) occur throughout tropical and subtropical regions of the world where they infect 100s of millions of people annually. In Australia, the dengue receptive zone is confined to the northern state of Queensland where the principal vector Aedes aegypti (L.) is present. In the current study, two populations of Ae. aegypti from north Queensland were exposed to two urban outbreak strains and one sylvatic strain of dengue virus type 2 (DENV-2). The titer of virus required to infect 50% of mosquitoes was between 10 5 and 10 6 50% tissue culture infectious dose (TCID)50 /ml and was influenced by the combination of the origin of Ae. aegypti population and virus strain. When exposed to infectious bloodmeal titers > 10 6 TCID50 /ml, infection and dissemination rates were all > 50% and were significantly affected by the origin of the mosquito population but not by the strain of DENV-2. Replication of DENV-2 was also significantly affected by the mosquito population and the titer of the infectious bloodmeal that mosquitoes were exposed to. The results of this study are discussed in the context of DENV transmission dynamics in northern Australia and the relative fitness of the sylvatic virus strain in urban Ae. aegypti populations.